2016
DOI: 10.1097/meg.0000000000000642
|View full text |Cite
|
Sign up to set email alerts
|

MRI characteristics for the differential diagnosis of benign and malignant small solitary hypovascular hepatic nodules

Abstract: PurposeTo compare the MRI findings of benign and malignant solitary hypovascular hepatic nodules and identify the differentiating features.Materials and methodsA total of 135 patients with solitary hypovascular hepatic lesions up to 3 cm (mass forming intrahepatic cholangiocarcinoma, n=29; metastases, n=26; inflammatory pseudotumors and solitary necrotic nodule, n=48; and hemangioma, n=32) were assessed. MRI findings were analyzed, and lesions were scored for peripheral and intratumoral appearance and enhancem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2017
2017
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 34 publications
0
10
0
Order By: Relevance
“…MR images: On T1 gradient echo before gadolinium, the lesion shows a slightly hypointense signal (black arrow) a; after Gd-BOPTA administration, no contrast enhancement can be seen (black arrow) b, c, d; thin rim enhancement (arrowheads) is seen in the delayed phase e; in the hepatobiliary phases, the fill-in pattern is also not observed (black arrow) f. can reliably assess arterial phase enhancement on continuous image acquisition from the arrival of the first microbubbles to peak arterial enhancement. Indeed, the US contrast agent avalaible in our country (i. e. SonoVue) is a purely blood pool agent, that lacks extravascular interstitial diffusion that is best appreciated by MRI in late scans [23][24][25] and, even better, in delayed and very delayed scans [26].…”
Section: Discussionmentioning
confidence: 99%
“…MR images: On T1 gradient echo before gadolinium, the lesion shows a slightly hypointense signal (black arrow) a; after Gd-BOPTA administration, no contrast enhancement can be seen (black arrow) b, c, d; thin rim enhancement (arrowheads) is seen in the delayed phase e; in the hepatobiliary phases, the fill-in pattern is also not observed (black arrow) f. can reliably assess arterial phase enhancement on continuous image acquisition from the arrival of the first microbubbles to peak arterial enhancement. Indeed, the US contrast agent avalaible in our country (i. e. SonoVue) is a purely blood pool agent, that lacks extravascular interstitial diffusion that is best appreciated by MRI in late scans [23][24][25] and, even better, in delayed and very delayed scans [26].…”
Section: Discussionmentioning
confidence: 99%
“…1-A proper contrast-enhanced CT/MRI examination with a state-of-the art apparatus is mandatory for proper characterization of liver lesions, particularly in patients with chronic viral hepatitis (22)(23)(24)(25). According to recent data, an MRI examination with a hepatocyte-specific agent is preferred (26,27). 2-Even the most specific examination method may fail in rare situations (27), especially outside academic centers.…”
Section: Discussionmentioning
confidence: 99%
“…According to recent data, an MRI examination with a hepatocyte-specific agent is preferred (26,27). 2-Even the most specific examination method may fail in rare situations (27), especially outside academic centers. The suggestion stated by Portolani et al (16) to repeat the imaging examination 4-6 months later is a practical safeguard.…”
Section: Discussionmentioning
confidence: 99%
“…Small hepatic lesions can be more challenging to characterize. Several studies have shown that small intrahepatic cholangiocarcinoma, hemangioma, and metastases may mimic the enhancement characteristics of HCC (18)(19)(20). Unlike the LI-RADS 5 category, which has a low cut-off value for diameter (1 cm), LI-RADS 4 applies the same high probability of HCC for lesions of varying sizes, including those with a diameter of <1 cm.…”
Section: Discussionmentioning
confidence: 99%